Coping Strategies and Stress in a Group of Children in the City of San Luis (Argentina) - Arrieta, Gisela Anahí; Baldi López, Graciela; Albanesi de Nasetta, Susana (Pensando Psicología, 2015)
Introduction: Stress is a problem that also affects children. It manifests itself in them through a series of reactions, both at the biological and psychological levels, in situations that feel uncontrollable. In childhood, children have to put into practice diverse coping strategies and cognitive-behavioral efforts to overcome changes inherent to that phase.Objectives: Examine coping strategies used by a group of children of both genders in the city of San Luis, Argentina, and detect relationships between coping strategies, gender and the level of stress experienced.Methodology: The non-probabilistic-intentional sample consisted of 106 children (between the ages of 8 and 12), who attended two educational establishments in the city. The Children’s Daily Stress Inventory and the Situational Coping Strategies Questionnaire were applied among boys and girls.Results and discussion: The most often used coping strategies were active (such as seeking information and support) and emotional to reduce stress. Differences were found in the use of coping strategies in relation to gender and the level of stress experienced by the children.
Keywords: stress; coping strategies; gender; childhood